Crystal Growth Kinetics in GeS2 Glass and Viscosity of Supercooled Liquid - Málek, Jiří; Podzemná, Veronika; Shánělová, Jana (American Chemical Society, 2021)
The crystal growth kinetics and morphology in germanium disulfide bulk glass and glass surface is described. The structural relaxation taking place below the glass transition is slow and the corresponding volumetric change is negligible. Therefore, it does not affect substantially the crystal growth process. The crystal growth rate of low temperature beta-GeS2 and high temperature alpha-GeS2 polymorphs in the bulk glass is comparable, being slightly decoupled from the shear viscosity below the glass transition. The crystal growth rate of beta-GeS2 in an amorphous thin film of the same composition is several orders of magnitude faster than that at the surface of bulk glass. This fast surface crystal growth is strongly decoupled from viscosity. Such behavior resembles the glass-to-crystal fast growth mode observed by several authors in some organic molecular glasses. Taking into account previously reported viscosity and heat capacity data, the crystal growth kinetics of both polymorphs can be quantitatively described by the 2D surface growth model for low and high supercooling. The nonisothermal differential scanning calorimetry experiments are analyzed, providing evidence of a complex nature of the overall crystallization process with apparent activation energy comparable to that obtained from isothermal microscopy measurement of crystal growth in the same temperature range.
Krystalový růst v GeS2 skle a viskozita podchlazené kapaliny
Keywords: medium-range order; crystallization kinetics; structural relaxation; temperature; sulfide; sulfur; transition; disulfide; density; kinetika krystalizace; růst krystalů; GeS2; sklo; viskozita; uspořádání